Observations on Basil II as Patron of the Arts - Riccardi, Lorenzo (Actual Problems of Theory and History of Art, 2025)
This communication is about the figure of Basil II as patron of the arts. Even though he is known as one of the most uncultivated sovereign in byzantine history, two wonderful manuscripts are linked to his name: the Menologium of the Vatican Apostolic Library and the Psalter of the Mariciana Library. The author tries to reconstruct the cultural and artistic activities of Basil II.